Anisotropic transition metal–based nanomaterials for biomedical applications. Issue 4 (12th May 2021) - Xu, Min; Song, Yiling; Wang, Jinping; Li, Nan
Abstract: Transition metal–based nanoparticles have attracted more and more attention in biomedicine, owing to their special characteristics that arise from finite‐size and surface effects, such as intense and broad light absorption, strong oxidation ability, catalytic activity, and robust mechanical properties. Researches on transition metal–based nanoparticles and their clinical applications have been, so far, mainly focus on the spherical shape. However, many efforts have been made to develop different anisotropic shapes to increase their physicochemical properties and biological activity. In this regard, it would be of great benefit to elaborate the recent developments, especially over the past 20 years, on the synthesis of anisotropic transition metal–based nanomaterials and their unique shape‐dependent properties, mechanism, as well as superiority and limitations in biomedicine, such as drug delivery, disease therapy, and resonance imaging. Here, we will summarize in detail the mechanism and advantages of three main shape categories of anisotropic transition metal–based nanomaterials in biomedical applications, including one‐dimensional (e.g., nanowire), two‐dimensional (e.g., nanosheet), and three‐dimensional (e.g., nanorod, nanocube, and nanoflower) anisotropic shapes. In addition, the critical challenges and prospects of this field will be also proposed and discussed. Abstract : In this review, the authors summarize in detail the mechanism and advantages of three main shape categories of anisotropic transition metal–based nanomaterials in biomedical applications, including one‐dimensional (e.g., nanowire), two‐dimensional (e.g., nanosheet), and three‐dimensional (e.g., nanorod, nanocube, and nanoflower) anisotropic shapes.